2021
DOI: 10.1080/07448481.2020.1869750
|View full text |Cite
|
Sign up to set email alerts
|

Substance use, sexual behavior, and general well-being of U.S. college students during the COVID-19 pandemic: A brief report

Abstract: This study gathered preliminary data on the impact of the U.S. response to the COVID-19 pandemic on the substance use, sexual behavior, and general well-being of U.S. college students. Participants from colleges across the U.S. (N ¼ 212; 50.5% female; M age ¼ 22.09) completed an online survey between May 20 th and July 5 th , 2020 about COVID-19-related behavior change. Most students reported a decrease in quality of life (71.7%), an increase in levels of anxiety (63.7%), and problems with basic resource needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 38 publications
7
47
1
Order By: Relevance
“…Furthermore, during the lockdown, there is a substantial risk of increasing substance use [ 21 ]. Interestingly, the pandemic has also influenced students’ sex lives, as most of them reported a decrease in sexual activity, yet use of dating apps remained unchanged [ 22 ]. Finally, the pandemic situation and lockdowns have also influenced students’ sleeping patterns—although they tend to spend more time in bed, overall sleep quality and insomnia symptoms have worsened [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during the lockdown, there is a substantial risk of increasing substance use [ 21 ]. Interestingly, the pandemic has also influenced students’ sex lives, as most of them reported a decrease in sexual activity, yet use of dating apps remained unchanged [ 22 ]. Finally, the pandemic situation and lockdowns have also influenced students’ sleeping patterns—although they tend to spend more time in bed, overall sleep quality and insomnia symptoms have worsened [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A growing literature has investigated the effects of the pandemic on alcohol use among adolescents, young adults, and college students in the U.S. and found mixed results [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. Decreases in opportunities to socialize related to the pandemic were associated with decreases in alcohol use among college students [ 11 , 12 , 18 , 20 ].…”
mentioning
confidence: 99%
“…In one study of adolescent sexual minority males, participants reported seeing their sexual partners less often during the COVID-19 pandemic [17]. In another study with college students aged 18-25, most students reported a decrease in sexual activity [18]. Just as patterns of relationship involvement and sexual activity vary between adolescence and young adulthood [19,20], additional research is needed to compare the pandemic's impact on romantic and sexual relationships by age.…”
Section: Introductionmentioning
confidence: 99%
“…* p-value based on chi-square test comparing adolescents (ages 13-17) and young adults (ages[18][19][20][21] …”
mentioning
confidence: 99%
See 1 more Smart Citation